Position of personality in communication and analysis of co-managing behavior in older adolescents - Efimova I. A. (Socio-Pedagogical Issues of Education and Upbringing, 2025)
This article examines the preferred coping strategies (coping behavior) of adolescents through the theory of personality in the concept of transactional analysis. Recommendations are given for working with coping strategies of adolescents, which are important in the work of a psychologist.
Keywords: стрессоустойчивость; копинг-стратегии; жизнестойкость; совладающее поведение; теория личности; coping behavior; трудные подростки; transactional analysis; stress resistance; coping strategies; транзактный анализ; difficult teenagers; personality theory; resilience